Structural properties of Bi/Au(110). (4th June 2023) - Neziri, Egzona; Zhang, Wei; Smogunov, Alexander; Mayne, Andrew J; Kara, Abdelkader; Dappe, Yannick J; Oughaddou, Hamid
Abstract: Atomically thin bismuth films (2D Bi) are becoming a promising research area due to their unique properties and their wide variety of applications in spintronics, electronic and optoelectronic devices. We report on the structural properties of Bi on Au(110), explored by low-energy electron diffraction (LEED), scanning tunneling microscopy (STM) and density functional theory (DFT) calculations. At a Bi coverage lower than one monolayer (1 ML) various reconstructions are observed, we focus on Bi/Au(110)-c(2 × 2) reconstruction (at 0.5 ML) and Bi/Au(110)-(3 × 3) structure (at 0.66 ML). We propose models for both structures based on STM measurements and further confirm by DFT calculations.